Teknik Penentuan Arah Kiblat Menggunakan Aplikasi Google Earth dan Kompas Kiblat RHI - Mustofa Kamal (Madaniyah, 2015)
The direction of the Qibla prayer at mosques and prayer rooms in Blendung Village, Ulujami Subdistrict, Pemalang Regency is different, some are straight to adjust the direction of the building and the direction of the ceramic floor, some are leaning towards the right. The difference in the direction of this Qibla is the background for conducting research, with a focus on the direction of the mosque and mosque building and the direction of the Qibla shoff at the mosque and mosque. This field research was sourced from the main data from the results of the accuracy of the direction of the mosque and the prayer room, information from the management of the mosque and the mosque and those who know the history of the mosque and mosque. Data processing is done by triangulation techniques. Qibla direction accuracy test uses measurement method with RHI Qibla compass and Google Earth application. Azimuth Qibla of Blendung Village area is at coordinates 293.5o (Kompas Qibla RHI) or coordinate point 294.67o (Google Earth). From the analysis of the data that was conducted showed that not all mosque and musholla buildings were aligned to lead to Qibla. Based on data and analysis results of two mosques and nine small mosque in Blendung Village, six mosque buildings and small mosque are parallel to the straight direction of the Qibla, three buildings show a precise level of alignment, while the other three are at one degree. the other five buildings strayed from the Qibla direction in the range of 17o-26o. The direction of building the Islahul Hayat mosque is highest (26o) compared to the direction of other buildings. In terms of the Qibla direction, the two mosques are already leading to Qibla. Six mushollas have headed to the Qibla in the range of 0o-2o, and three musholla deviated in varying ranges, Al-Arofah Al-7o, Al-Ihsan + 7o and Nurul Ihsan + 18o. The direction of the building and the Qibla direction parallel to the Qibla are the Jami ’Al-Azhar Mosque, Al-Ikhlas Mosque, Tsamrotul Bahri Mosque and At-Taqwa Mosque.